APPEARANCE OF MAKSUD KARYIEV'S STYLE IN "IBN SINO" NOVEL (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article analyzes some of the writer's unique styles in Maqsud Qariyev's novel "Ibn Sino".